2014
DOI: 10.7314/apjcp.2014.15.15.6211
|View full text |Cite
|
Sign up to set email alerts
|

Associations between AT-rich Interactive Domain 5B gene Polymorphisms and Risk of Childhood Acute Lymphoblastic Leukemia: a Meta-analysis

Abstract: Asian Pac J Cancer Prev, 15 (15), 6211-6217 IntroductionAcute lymphoblastic leukemia (ALL), the most common malignancy in children (Linabery and Ross, 2008;Jiang et al., 2013), is a heterogeneous disease, with respect to its underlying cellular and molecular biology (Papaemmanuil et al., 2009), acquired genetic abnormalities, and social clinical responses to combination chemotherapy (Pui et al., 2004). The mechanisms involved in the etiology of childhood ALL remain obscure. It is hypothesized that both environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Forty-two genes were considered biological ALL risk genes. In line with several metanalyses, we found that ARID5B was the most plausible gene [14][15][16].…”
Section: Discussionsupporting
confidence: 85%
“…Forty-two genes were considered biological ALL risk genes. In line with several metanalyses, we found that ARID5B was the most plausible gene [14][15][16].…”
Section: Discussionsupporting
confidence: 85%
“…In a previous study, they reported the association between rs2393782 and rs4948488 with the risk to -León et al, 2019). Previous research studies showed that ARID5B rs7089424 and rs10994982 were associated with the risk of B-ALL development (Zeng et al, 2014). This might be explained by the role of recombination activation gene (RAG1) in early B-cell differentiation (Tao et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The specific function of this highly conserved element has not been fully elucidated, but it is located between ARID5B and RTKN2 ( Jiang et al, 2014 ), both of which have been linked to roles in regulation of immune responses. ARID5B encodes a DNA-binding protein with roles in NK cell function ( Cichocki et al, 2018 ), cancers of both B and T lymphocytes ( Healy et al, 2010 ; Zeng et al, 2014 ; Leong et al, 2017 ), and autoimmune disease ( Wang et al, 2012 ; Yang et al, 2013 ). The RTKN2 gene is expressed in lymphocytes ( Collier et al, 2004 ), induces an NF-kB-dependent hold on apoptosis ( Collier et al, 2009 ) that can change counts and function of available immune cells, and has been implicated in autoimmune disease ( Myouzen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%